A STUDY OF FACTORS AFFECTING ENTREPRENEURIAL INTENTION: THE MODERATING ROLE OF INDIVIDUALISM - AL, MUAZAM; OMAR, SITI SARAH; SADAF GHUFFAR, SADAF GHUFFAR; AHMAD, IDAYUWATI; MAJEED HAMAWANDY, NAWZAD (2023)
The main purpose of this study is to identify the factors which affect the entrepreneurial intention (EI) of the university students of Gilgit-Baltistan. This research study mainly focuses on the theory of planned behaviour (TPB) and Hofstede national culture dimension of individualism. The quantitative research method was applied for the data analysis. The data were collected from the public sector universities of Gilgit-Baltistan with the total number of 362 final year students. Moreover, to test the hypothesis of the study structural equation modeling (PLS-SEM) version 4.0 software were used for the data analysis and interpretation. The findings of the research are follows: i) attitude towards behaviour positively influence the entrepreneurial intention of the university students ii) subjective norms also significantly affect the entrepreneurial intention iii) perceived behaviour control has a positive effect on the entrepreneurial intention of the university students. However, the moderating variable of individualism does not moderate the relationship between TPB and EI. Moreover, this research study provides a comprehensive research model which includes the behavioural, and culture factors that were analyzed and validated through empirical evidence. It is also one of the pioneer research conducted in the rural areas i.e. Gilgit-Baltistan of Pakistan.